Emergency and seedling growth of sweet passion fruit according to sewage sludge and light - Freitas, Allan Rocha de; Lopes, José Carlos; Alexandre, Rodrigo Sobreira; Venancio, Luan Peroni; Zanotti, Rafael Fonsêca (Comunicata Scientiae, 2015)
The species Passiflora alata Curtis is native from Brazil and provides good growth by finding suitable ecological conditions. The objective of this study was to evaluate the emergence of seeds and growth of seedlings of sweet passion in soils fertilized with sewage sludge under different luminous intensity. The experiment was conducted in Laboratório de Análise de Sementes in a greenhouse at the Center for Agricultural Sciences, Universidade Federal do Espírito Santo (CCA-UFES), AlegreES. The treatments were arranged in a factorial design (6x4) consisting of two soil types (Typic and Oxisol) + sewage sludge: without sludge, with sludge and sludge-amended with limestone under the four luminous intensity [full sun (0,85 μmol m-2 s-1), cover with a black mesh (0,74 μmol m-2 s-1); cover with two black screen (0,70 μmol m-2 s-1) and cover with three black screen (0,40 μmol m-2 s-1). The cultivation of sweet passion fruit in soils treated with sewage sludge, the plants have increased growth. The use of two or three black screens (0.70 and 0.40 μmol m-2 s-1), respectively, provided greater vegetative growth of seedlings of sweet passion fruit.